Budget Management of the Aceh Government: An Analysis of the Maqāṣid al-sharī’ah Approach - Ayumiati, Ayumiati; Fahlevi, Heru; Yasir Yusuf, Muhammad; Abdullah, Syukriy (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Aceh is a region that has special autonomy and privileges based on law within the Unitary State of the Republic of Indonesia. In terms of the application of the special autonomy, four pillars shall be enacted by the government, including the implementation of religious life and the role of religious scholars in making regional policies in the context of Islamic law. This present study aims to examine the realization of regional expenditures based on their functions in accordance with the maqāṣid al-sharī’ah (objectives of the Islamic law). This normative legal study analyzed data by using the theory of maqāṣid al-sharī’ah. The data consisted of documents such as Aceh Regional Revenue and Expenditure Budget (APBA) reports, legislations, and relevant articles and books. The findings of the study revealed that the determination of regional expenditures has been moderate and reflected the realization of the maqāṣid al-sharī’ah, although less optimal. In addition, the implementation of APBA management has been in line with the maqāṣid al-sharī’ah, including protecting soul, property, religion, mind, and lineage. Yet, in the concept of maqāṣid al-sharī’ah, the proposed order should be protecting religion, soul, mind, lineage, and then property. Despite following the maqāṣid al-sharī’ah, the order of the implementation of APBA management differs from that developed by Muslim scholars. However, such hierarchical order needs not to be understood as is, since in certain conditions (i.e., emergency), protecting soul should be more prioritized than protecting religion. Moreover, the category of budget management cannot be distinguished diametrically, i.e., protection of mind also includes protection of religion since it involves funding for education and dayah (Islamic boarding schools).